MultiPhase pulse flow pump warning system based on movement detection / Mohamad Mazwan Mahat … [et al.] - Mahat, Mohamad Mazwan; Saedon, Dr Juri; Bahsan, Rosnadiah; Makhtar, Ahmad Khushairy (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
This project developed and fabricated a new device that used to solve common problems for heart failure patients. The aim of this project is to obtain the effect of fluid characteristics of pressure and velocity in valve less impedance pump using pulsation flow based on different voltage supply and frequency. When the fluid-filled elastic tube is connected to a tube that has different impedance, net flow in either direction can be induced by periodically pinching the flexible tube asymmetrically from the end. In addition, it is also intended to determine the fluid volume flow rates (ml/min) in elastic tubes based upon different impedance pump pinch parameters (location and width). The input parameters evaluated are pinch frequency, voltage, pinch location, pincher width, elastic tube length and viscosity. This project uses experimental results as the approach to establish the relationship between the parameters. It is found that parameters like flow rate, velocity and pressure increase when the pinch location of the elastic tube is varied. The interaction with the inertia of the returning flow is an important factor determining the average flow for a closed loop system. The final product outcome from this experiment can be used as a model for a new Ventricular Assist Device for cardiac patients. It also can give further explanation about the factors that will influence the characteristics of valve less impedance pump.